Eight Laws of Logic for the Forensic Construction Expert - A. Yu. Butyrin; E. B. Stativa; O. A. Manukhina (Теория и практика судебной экспертизы, 2021)
Forensic experts’ primary and additional professional education does not include such a subject as logic. At the same time, knowledge of logic is crucial at all stages of the examination process. Filling this gap, the authors of this article reveal the content of the fundamental laws of logic and demonstrate their role in the cognitive activity of knowledgeable persons who implement their specialized (primarily construction and technical) knowledge in court proceedings. This paper deals successively with such laws of logic as the law of identity, the law of contradiction, the law of the excluded middle, the law of sufficient reason, the law of double negation, Clavius’s law, the law of contraposition, and laws of division (the dichotomy of logic) concerning various investigative and forensic situations. The projection of these laws of logic on the intellectual operations performed by experts will allow, from the authors’ point of view, to give the process of forensic examinations greater clarity and consistency, which, ultimately, should ensure an increase in its efficiency and quality of results. Logically verified approaches to work will also reduce time and financial costs.